Husband’s Nusyuz in Female-Initiated Divorce: A Mubadalah Perspective - Ifada Azka Ahyu; Jamilah Jamilah; Yusmita Yusmita; Ilham Saeful Malik (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
Many people believe that Nusyuz (marital disobedience) is only committed by wives against their husbands, overlooking the possibility of Nusyuz by husbands towards their wives. Similarly, the judges at the Banyuwangi Religious Court often interpret divorce cases initiated by wives as a sign of the wife’s Nusyuz, even when the divorce is caused by the husband’s Nusyuz. This forms the background of this research. The focus and aim of this study are to analyze the judges' perspectives at the Banyuwangi Religious Court regarding the consideration of a husband’s Nusyuz, the status of a husband’s Nusyuz in divorce cases heard at the court, and to evaluate the judges' views on Nusyuz through the lens of mubadalah (reciprocity in marriage). This empirical juridical research adopts a qualitative approach, utilizing interviews with judges at the Banyuwangi Religious Court. The data used in this study includes primary, secondary, and tertiary sources. The research findings reveal that: (1) The majority of judges at the Banyuwangi Religious Court consider a husband’s Nusyuz primarily through the concept of taklik talak (conditional divorce). (2) In divorce cases at the Banyuwangi Religious Court, judges often deny post-divorce rights to wives, assuming that a wife who files for divorce is guilty of Nusyuz. As a result, they do not grant post-divorce entitlements such as mut’ah (compensation) and iddah (waiting period) maintenance. Although most judges at the Banyuwangi Religious Court understand the concept of Nusyuz from a mubadalah perspective, they have yet to fully implement it in practice